DEVELOPING A COMMUNITY ASSESSMENT FOR PUBLIC HEALTH EMERGENCY RESPONSE PROTOCOL FOR THE RILEY COUNTY HEALTH DEPARTMENT - Sello, Mamakase Sello (My University, 2021)
Community Assessment for Public Health Emergency Response (CASPER) is a specific set of epidemiologic tools and methods designed by the Centers for Disease Control and Prevention (CDC) to provide decision-makers with rapid, inexpensive, accurate, and reliable population-based public health information about communities affected by disasters. The CASPER method and tools can be utilized to quickly measure the basic needs and health status of a community affected by a disaster by providing objective information required to allocate resources and assets during all disaster phases. The primary objective of this project was to create a simplified local CASPER process for Riley County, Kansas. The development of the CASPER process for the Riley County Health Department (RCHD) closely followed the CDC CASPER toolkit operations sections. This CASPER process was pilot tested to determine if it would be a useful tool for RCHD to measure the community's basic needs and health status. The CASPER process involves conducting door-to-door surveys or a random sample of households using a questionnaire. CASPER tools include site selection tools, questionnaires, data analysis templates, and paper-based or electronic devices for data collection. Although the CDC developed the CASPER toolkit specifically for use in communities affected by disasters, other health departments adapted the use of CASPER to collect primary data about public health needs as part of a Community Health Assessment (CHA). In non-disaster settings, health departments and organizations can use the CASPER methodology to answer other preparedness and research questions. Other public health departments have indicated that CASPER can be a useful tool for assessing health needs in various settings, including non-disaster settings. The CASPER protocol developed for Riley County, Kansas, is a promising tool for gathering information to allocate limited county and state resources to meet the most immediate needs of Riley County residents.
Keywords: CASPER; epidemiology information; toolkit